Copy number variation and warfarin dosing: evaluation of CYP2C9, VKORC1, CYP4F2, GGCX and CALU. (February 2012) - Scott, Stuart A; Patel, Manishkumar; Martis, Suparna; Lubitz, Steven A; van der Zee, Sarina; Yoo, Chang; Edelmann, Lisa; Halperin, Jonathan L; Desnick, Robert J
Aim: To determine if copy number variants contribute to warfarin dose requirements, we investigated CYP2C9, VKORC1, CYP4F2, GGCX and CALU for deletions and duplications in a multiethnic patient population treated with therapeutic doses of warfarin.Patients & methods: DNA samples from 178 patients were subjected to copy number analyses by multiplex ligation-dependent probe amplification or quantitative PCR assays. Additionally, the CYP2C9 exon 8 insertion/deletion polymorphism (rs71668942) was examined among the patient cohort and 1750 additional multiethnic healthy individuals.Results: All patients carried two copies of CYP2C9 by multiplex ligation-dependent probe amplification and no exon 8 deletion carriers were detected. Similarly, quantitative PCR assays for VKORC1, CYP4F2, GGCX and CALU identified two copies in all populations.Conclusion: These data indicate that copy number variants in the principal genes involved in warfarin dose variability ( CYP2C9, VKORC1 ), including genes with lesser effect ( CYP4F2, GGCX ), and those that may be more relevant among certain racial groups ( CALU ), are rare in multiethnic populations, including African–Americans. Original submitted 5 August 2011; Revision submitted 26 October 2011